Gge Biplot and Ammi Analysis of Yield of Proso Millet (Panicum Miliaceum L.) - Raihan, HUZ; Billah, MM; Riad, MI; Sarker, MB; Rohman, MM (Bangladesh Journal of Agricultural Research, 2023)
The experiment was conducted using seven proso millet advanced lines including one check variety, BARI Cheena-1 (BC-1) across 3 locations (Gazipur, Jamalpur and Rangpur) of Bangladesh during 2019-20. The objective of this study was to find out stable proso millet lines, and to verify the influence of the environments on the yield at different locations of Bangladesh. The mean sum of squares for the genotypes were significant for grain yield which revealed the presence of genetic variability in the material under studied. The results of the AMMI analysis indicated that the main effects due to genotype (G), environment (E) and GE interaction were significant, representing differential responses of the lines to the varied environments. Based on the AMMI stability parameter BD-1447, BD-1411 and BD-777 were the most stable lines across the environments, of which BD-777 was most stable. Biplot showed that the environment of Rangpur was poor; but that of Gazipur and Jamalpur were better for proso millet cultivation. Results also suggested that BD-1447, BD-1411 and BD-777 could be included in breeding programs due to their higher grain yield. Bangladesh J. Agril. Res. 46(2): 133-142, June 2021